A case report of Lithium induced Dariers disease - Dinesh Kumar MK (Kerala Journal of Psychiatry, 2020)
Lithium has been used frequently in the management of Affective disorders since six decades and known to cause dermatological adverse events in the form of Acne, exacerbation of Psoriasis etc..Here we report another dermatological manifestation of Lithium therapy, induction of Dariers disease.